William Wordsworth and modern travel railways, motorcars and the Lake District, 1830-1940. - Yoshikawa, Saeko (Liverpool University Press, 2020)
This book explores Wordsworth's extraordinary influence on the tourist landscape of the Lake District throughout the age of railways, motorcars and the First World War. It explores how patterns of tourist behaviour and environmental awareness changed in the century of popular tourism, examining how Wordsworth's vision shaped modern ideas of travel, landscape and cultural heritage.
Keywords: Wordsworth, William, -- 1770-1850 -- Influence.; Wordsworth, William, -- 1770-1850; Lake District (England); Tourism -- England -- History.; Lake District (Angleterre); Influence (Literary, artistic, etc.); Tourism; England; England -- Lake District; History